Species composition and diversity of cast net fisheries in New Calabar River, Niger Delta, Nigeria (Journal of Biodiversity Conservation and Bioresource Management, 2018)
A study on the catch composition and diversity of cast net fisheries was conducted between May and August, 2017 in the New Calabar River, Rivers state, using cast net of varying mesh sizes (1.5mm and 2.5mm). Fish samples were collected from three sampling stations, viz. Station1- Aluu, Station 2- Choba and Station 3- Iwofe. The fish species recorded comprised of 26 species under 11 families, and one decapod crustacean. The three most abundant species were; Coptodon guineensis (25.11%), Coptodon zilli (18.56%) both from the Cichlidae family, and Penaeus nitialis (10.90%) from the Penaeidae family, while the least abundant species was Liza grandisquamis (0.13%) from the Mugilidae family. The diversity indices showed that station 2 recorded the highest number of species (21) while station 1 recorded the lowest with (12) species. Simpson’s indexes of diversity, Simpson’s reciprocal index, Shannon- weiner index, and Pielou’s evenness index, were estimated. This study serves as a base line data which will assist relevant bodies in the management and conservation of fisheries resources in the New Calabar River. It is therefore recommended that for an improved and sustainable exploitation and management of fisheries resources of the New Calabar River, proper monitoring and management for fish stock must be done.J. Biodivers. Conserv. Bioresour. Manag. 2018, 4(1): 19-26